Transposition flap for reconstruction of lower eyelid wounds adjacent to the tarsus after Mohs micrographic surgery: a case series - Bruna Cabral Meira Chaves; Luciana Ballardin; Felipe Bochnia Cerci (Surgical & Cosmetic Dermatology)
Skin cancers affecting the eyelid can be a reconstructive challenge due to the complexity of the local anatomy. In addition to precise eradication of the tumor, maximal preservation of the skin is essential for both functional and cosmetic outcomes. Transposition flaps represent an excellent reconstructive option, as they require few incisions and, when well planned, do not cause ectropion, a key consideration in this topography. We describe a case series of lower eyelid reconstructions adjacent to the tarsus following Mohs micrographic surgery, using transposition flaps.